The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1017/s0033291719003982
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic, long-term follow-up of purging disorder

Abstract: Background The DSM-5 introduced purging disorder (PD) as an other specified feeding or eating disorder characterized by recurrent purging in the absence of binge eating. The current study sought to describe the long-term outcome of PD and to examine predictors of outcome. Methods Women (N = 84) who met research criteria for PD completed a comprehensive battery of baseline interview and questionnaire assessments. At an average of 10.24 (3.81) years follow-up, available records indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Consistent with prior work (Forney et al, 2021), three outcome definitions were tested. An eating disorder was diagnosed as present if an individual met DSM-5 criteria for anorexia nervosa, bulimia nervosa, binge-eating disorder, purging disorder, or another OSFED.…”
Section: Outcome Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with prior work (Forney et al, 2021), three outcome definitions were tested. An eating disorder was diagnosed as present if an individual met DSM-5 criteria for anorexia nervosa, bulimia nervosa, binge-eating disorder, purging disorder, or another OSFED.…”
Section: Outcome Definitionsmentioning
confidence: 99%
“…We recently published results describing the naturalistic outcome of purging disorder at an average of 10‐year follow‐up (Forney et al, 2021). Despite experiencing a significant decrease in eating pathology, women with purging disorder reported a relatively poor outcome; 58% continued to meet criteria for an eating disorder, and only 30% met criteria for full recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that peer-led Body Project groups produced a statistically significant 46% reduction in onset of subthreshold/threshold BN and a statistically significant 62% reduction in onset of PD relative to controls during the follow-up period. These prevention effects are critical, given that <50% of individuals who experience BN or PD achieve full recovery (Forney, Crosby, Brown, Klein, & Keel, 2021 ; Steinhausen & Weber, 2009 ). In addition to high rates of comorbidity and physical consequences, BN has been independently associated with suicidality above and beyond risk predicted by comorbid disorders (Bodell, Joiner, & Keel, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from participants in the current study were included in prior analyses to examine whether postprandial peptide YY (PYY) and ghrelin responses contributed to differences in subjective responses to a fixed test meal (Keel et al, 2018a ) and whether a behavioral measure of satiation using an ad lib meal confirmed self-reported responses to a fixed meal (Keel et al, 2018b ). Data from these participants were also included in secondary analyses unrelated to the aims of the parent project (Davis, Smith, & Keel, 2020 ; Forney, Crosby, Brown, Klein, & Keel, 2021 ; Keel, Bodell, Haedt-Matt, Williams, & Appelbaum, 2017 ; Maske, Williams, & Keel, 2020 ). This is the first report of gastric emptying and of responses to the fixed meal in the medicated condition from this sample.…”
mentioning
confidence: 99%